2012
DOI: 10.1111/j.1445-5994.2012.02798.x
|View full text |Cite
|
Sign up to set email alerts
|

Single centre experience with pegylated interferon and ribavirin for hepatitis C: looking back before moving forward

Abstract: Background:  Hepatitis C treatment is successful in 40–80% of patients in drug sponsored registration trials. However, few studies have examined treatment outcomes in non‐trial, routine clinical practice settings. Aim:  The aim of this study was to investigate the treatment outcomes and predictors of a sustained virological response in a routine clinical setting. Methods:  Data were collected retrospectively on patients treated for hepatitis C between January 2004 and March 2010 in a tertiary hospital setting.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2014
2014
2014
2014

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 46 publications
(64 reference statements)
1
4
0
1
Order By: Relevance
“…Our results regarding genotypes as the strong predictors of SVR correspond to the data of the majority of other investigators obtained in RCT and in "real life" studies [10,24,25,28,31,32,33,40,42,46,[48][49][50].…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Our results regarding genotypes as the strong predictors of SVR correspond to the data of the majority of other investigators obtained in RCT and in "real life" studies [10,24,25,28,31,32,33,40,42,46,[48][49][50].…”
Section: Discussionsupporting
confidence: 89%
“…Danish nationwide cohort study [38], presented the data obtained in a routine clinical practice and found them comparable to those observed in controlled clinical trials: overall 57.9 % of patients achieved SVR: it was 46.5 % in patients with genotype 1/4 infection and 77.3 % in those with genotype 2/3 infection. Some other authors [39][40][41][42][43][44][45] and community based studies in Germany, Canada, France and Australia [46][47][48][49][50][51] reported SVR data comparable with those in RCT too. Conversely, results of other investigators were lower [52,53].…”
Section: Discussionmentioning
confidence: 89%
See 1 more Smart Citation
“…Forty patients were either lost to follow-up (10), early non-responders (14), or ceased treatment early due to side effects (16). Four patients completed treatment but had no end of treatment data available, and 4 patients who ceased treatment early due to side effects had end of treatment data available (Figure 1).…”
Section: Virological Responses and Predictorsmentioning
confidence: 99%
“…7 Published clinical trials of the treatment of HCV tend to have more favorable outcomes and are largely multicenter prospective pharmaceutical registration trials, which assess treatment response in treatment-na € õve patients with strict exclusion criteria and differences in treatment conditions. [8][9][10][11][12] To date, there have only been 2 single-centered retrospective audits of HCV treatment in Australia, 13,14 and one multi-centre study, 15 of 'real-world' patients treated in normal clinical practice. Often single hospitals have limited nursing and medical resources compared to large multinational clinical trials, which may affect patient retention in HCV therapy.…”
mentioning
confidence: 99%